2001
DOI: 10.1007/s002130100720
|View full text |Cite
|
Sign up to set email alerts
|

Environmental enrichment decreases intravenous self-administration of amphetamine in female and male rats

Abstract: These results suggest that environmental enrichment may serve as a protective factor for reducing amphetamine self-administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
122
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(139 citation statements)
references
References 44 publications
11
122
6
Order By: Relevance
“…Initially, there were significant housing differences during the 30-min habituation to the locomotor cages with higher activity in the HAn- SE relative to HAn-EE rats. These results are not in agreement with that of others, demonstrating no differences in activity levels between animals showing high (HAB) and low anxiety-like behavior (LAB) [19]. The findings are consistent with the reported differences in activity in the EPM for the HAn animals in the current study.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Initially, there were significant housing differences during the 30-min habituation to the locomotor cages with higher activity in the HAn- SE relative to HAn-EE rats. These results are not in agreement with that of others, demonstrating no differences in activity levels between animals showing high (HAB) and low anxiety-like behavior (LAB) [19]. The findings are consistent with the reported differences in activity in the EPM for the HAn animals in the current study.…”
Section: Discussioncontrasting
confidence: 54%
“…Postnatal environments that are enriched (e.g., toys, wheels) can influence an animal’s coping skills [16] as well as its vulnerability to drugs of abuse such as cocaine [17], morphine [18] and amphetamine [19, 20]. Conflicting findings exist on enriched environment’s (EE) impact on stress with some reporting no difference in corticosterone levels at baseline or after stressor [21] and others indicating a reduction in Sprague-Dawley rats [22] or even elevated levels in enriched Wistar rats [23].…”
Section: Introductionmentioning
confidence: 99%
“…Although this is the only study to investigate the effects of pair bonding experience on the rewarding properties of drugs of abuse, previous studies have demonstrated that other social experiences/factors may also influence drug reward. For example, rats reared with multiple social cohorts self-administered less AMPH (Bardo et al, 2001) and cocaine (Schenk et al, 1987) over repeated sessions than rats reared alone. Similarly, rats reared in an enriched environment that contained novel objects and social cohorts self-administered less AMPH, extinguished self-administration behavior sooner, and required higher doses of AMPH to reinstate drug-seeking than did rats housed alone (Bardo et al, 2001; Green et al, 2002; Stairs et al, 2006; c.f., Schenk et al, 1988; Bardo et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…For example, rats reared with multiple social cohorts self-administered less AMPH (Bardo et al, 2001) and cocaine (Schenk et al, 1987) over repeated sessions than rats reared alone. Similarly, rats reared in an enriched environment that contained novel objects and social cohorts self-administered less AMPH, extinguished self-administration behavior sooner, and required higher doses of AMPH to reinstate drug-seeking than did rats housed alone (Bardo et al, 2001; Green et al, 2002; Stairs et al, 2006; c.f., Schenk et al, 1988; Bardo et al, 1995). Furthermore, female rats trained to lever-press for cocaine showed markedly fewer responses after becoming pregnant and following parturition (Hecht et al, 1999), suggesting that the reproductive process and neurobiological changes involved with maternal experience may decrease the reinforcing properties of cocaine.…”
Section: Discussionmentioning
confidence: 99%
“…The walls of one side chamber were decorated by horizontal blackand-white stripes, whereas vertical black-and-white stripes were used for the other side chamber. Our CPP procedure was modelled after a previous study [24]. On day 1, each male's initial compartment preference was tested ( pre-test).…”
Section: (B) Testosterone Dosementioning
confidence: 99%